Heterosexual Men and Parenthood Decision Making in South Africa: Attending to the Invisible Norm. (August 2013) - Morison, Tracy
This article reports on a qualitative study about male involvement in parenthood decision making (i.e., decisions related to becoming a first-time parent) in which the focus was on White, heterosexual men. Little is known about the roles and involvement of these men in decision-making processes. They comprise an invisible norm in research as heteronormative assumptions about parenthood cause them to be overlooked. This oversight—exacerbated by the pervasive problem perspective in social science—forms the research rationale. Conducted within a gender-relational framework, the study included 23 heterosexual, White South African women and men with a view to exploring how gender constructions influence this process and affect the gender power relations. Interviews with participants were analyzed using a narrative–discursive method and the findings show how an assumption of childbearing shaped the data and may have implications for female–male power relations in reproductive partnerships.